Femoral artery rupture during total hip arthroplasty. (1st August 2013) - Kakwani, Rajeshkumar; Duggan, John; Muller, Scott
Abstract : Vascular injuries are an uncommon but significant complication of total hip arthroplasty. We present a case of femoral artery rupture through an atherosclerotic plaque during primary total hip arthroplasty and a review of the published literature. The early recognition and prompt treatment of this complication can reduce the mortality and morbidity associated with this injury.